Responsibility for private sector adaptation to climate change - Tina Schneider (Ecology and Society, 2014)
The Intergovernmental Panel on Climate Change (2007) indicates that vulnerable industries should adapt to the increasing likelihood of extreme weather events along with slowly shifting mean annual temperatures and precipitation patterns, to prevent major damages or periods of inoperability in the future. Most articles in the literature on business management frame organizational adaptation to climate change as a private action. This makes adaptation the sole responsibility of a company, for its sole benefit, and overlooks the fact that some companies provide critical goods and services such a food, water, electricity, and medical care, that are so vital to society that even a short-term setback in operations could put public security at risk. This raises the following questions: (1) Who is responsible for climate change adaptation by private-sector suppliers of critical infrastructure? (2) How can those who are identified to be responsible, actually be held to assume their responsibility for adapting to climate change? These questions will be addressed through a comprehensive review of the literature on business management, complemented by a review of specialized literature on public management. This review leads to several conclusions. Even though tasks that formerly belonged to the state have been taken over by private companies, the state still holds ultimate responsibility in the event of failure of private-sector owned utilities, insofar as they are "critical infrastructure." Therefore, it remains the state's responsibility to foster adaptation to climate change with appropriate action. In theory, effective ways of assuming this responsibility, while enabling critical infrastructure providers the flexibility adapt to climate change, would be to delegate adaptation to an agency, or to conduct negotiations with stakeholders. In view of this theory, Germany will be used as a case study to demonstrate how private-sector critical infrastructure providers can plan and implement climate change adaptation in practice, through the regulatory modes of "negotiations" and "enforced self-regulation."